Ghadd al-Baṣar dalam Q.S. al-Nūr [24]: 30-31 dan Relevansinya terhadap Upaya Pencegahan Pelecehan Seksual - Wawan Kurniawan; Asep Abdul Muhyi (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2026)
Sexual harassment is a multidimensional social problem that is shaped not only by individual desire, but also by power relations, institutional silence, digital exposure, and weak ethical literacy. This article examines the concept of ghadd al-baṣar in Q.S. al-Nūr [24]: 30-31 through Abdul Mustaqim’s tafsīr maqāṣidī and analyzes its relevance to the prevention of sexual harassment in contemporary physical and digital spaces. This study employs a qualitative library research design. The data were analyzed descriptively and analytically through eight stages: thematic reading of the verses, linguistic examination of key terms, contextual analysis of qadīm and jadīd settings, distinction between wasīlah and ghāyah, identification of maqāṣid values, hierarchical mapping of maqāṣid, interdisciplinary reflection, and synthesis of contemporary implications. The findings show that ghadd al-baṣar functions as a wasīlah for protecting religious integrity, human dignity, psychological safety, reason, and lineage. Its main contribution lies in expanding the interpretation of ghadd al-baṣar from an individual ethic of visual restraint into a social-collective ethic that requires family education, institutional policy, digital literacy, and victim-sensitive prevention mechanisms. Thus, tafsīr maqāṣidī enables Q.S. al-Nūr [24]: 30-31 to be read as a preventive ethical framework without reducing sexual harassment merely to the issue of gaze.